Changes in the Austrian structure of wages, 1996-2002: evidence from linked employer-employee data - Wolfgang Pointner; Alfred Stiglbauer (European Central Bank (ECB), 2010)
Analyzing data from the Structure of Earnings Surveys we find that wage dispersion in Austria increased marginally between 1996 and 2002. There was an increase in the returns to education which accrued only to male workers. The positive effects of tenure and especially of experience on wages decreased over time. We adopt the Machado-Mata (2005) counterfactual decomposition technique which allows to attribute changes in each wage decile to changes in worker and workplace characteristics and into changes in returns to these characteristics. Behind the small net increase in inequality we document a number of interesting gross effects that influence the wage distribution. We find that both composition effects due to gender, education and age and market-driven effects such as changes in returns and changing workplace characteristics contributed to a higher dispersion of wages.
Keywords: J22; J31; 330; Machado-Mata decomposition; quantile regression; Wage Structure; Lohnstruktur; Österreich